Pengembangan Personal Branding dalam Pendidikan Islam di Indonesia - Nur Fatimah (Jurnal Pendidikan Islam, 2022)
This research is a literature study that aims to analyze studies on personal branding in the education area, especially islamic education in Indonesia. The search for the study was carried out online on the Google Scholar, Garuda and Moraref sites. To add insight into personal branding trends, a general search related to personal branding was also conducted, which resulted in findings that personal branding trends were found in the fields of business, politics and entertainment. Personal branding in the three fields has the same tendency, namely to use it as a strategy to influence people's perceptions of themselves and the products they produce. This study shows that personal branding is one of the soft skills development strategies for students. introduction training, The formation and development of personal branding is mostly done as an effort to provide students with insight into personal branding. With personal branding insight possessed by students, they are expected to be able to adapt and meet the demands of society and job seekers. In addition, educators also use personal branding as an effort to attract public interest in educational institutions and the learning materials it teaches.